IGCSE Students’ Attitudes toward Learning Accounting: Its Relation to their Competencies in Business Management - Guansi, Dr. Steve Salamat; Ebrahim, Mr. Emad Sadeq (IJRDO - Journal of Business Management, 2018)
The study entitled “IGCSE Students’ Attitude toward Learning Accounting: its Relation to their Competencies in Business Management”, analyzed and sought answers to the following problems: students’ attitudes toward learning accounting, students’ competencies in business management and determining the correlation of students’ attitude and their competencies in business. The study utilized the descriptive method of research and employed the use of survey– questionnaire as a primary data gathering, collected, analyzed and interpreted using descriptive for weighted means and inferential statistics for pearson’s correlation coefficient. The research made use of a non probability - purposive sampling and has included forty (40) respondents who were identified as IGCSE students and who are enrolled in the IGCSE program in the Kingdom of Bahrain.The study has inferred that IGCSE students’ attitude towards learning accounting as favorable in many ways such as accounting is very important, learning accounting leads students toward doing effective business and accounting becomes one of the great professions nowadays. This was concluded by the respondents with an average weighted mean of 4.17 and with a description of Agree (A). It was also noted that students’ competencies in business management can be achieved considerably such as developing and improving skills in entrepreneurship, marketing, organization, communications, interpersonal relations, leadership and literacy in technology and computers. This was inferred by the respondents with an average weighted mean of 4.22 and with a description of Agree (A).